Pain Management Adequacy in Patients With Bone Metastases: A Secondary Analysis From the Palliative Radiotherapy and Inflammation Study Trial - Savino Cilla; Romina Rossi; Costanza Maria Donati; Ragnhild Habberstad; Pal Klepstad; Monia Dall’Agata; Vanessa Valenti; Stein Kaasa; Federica Medici; Alessio Giuseppe Morganti; Marco Maltoni (Clinical Medicine Insights: Oncology)
Background: Bone metastases (BMs) are a common complication in patients with cancer, often leading to significant pain that adversely affects quality of life, necessitating effective pain management strategies. This study aims to evaluate the effectiveness of pain management in patients with BMs undergoing palliative radiotherapy and to identify determinants of pain management adequacy. Methods: We conducted an observational analysis of 560 patients from the Palliative Radiotherapy and Inflammation Study (PRAIS) trial across several European centers, focusing on the Pain Management Index (PMI) for assessing pain management adequacy. Key predictors examined included Karnofsky Performance Status (KPS), treatment setting, primary tumor type, and site of BMs. Results: Our findings indicate that 19.0% of patients experienced inadequate pain management (PMI < 0). Specifically, patients with KPS ⩾ 90 had a notably lower rate of adequate analgesic therapy (59.3%) compared with those with a KPS < 90 (85.0%). Among outpatients, 23.7% reported inadequate pain management, contrasted with a significantly lower inadequacy rate (3.8%) in palliative care or hospice settings. In addition, in outpatients, pain management adequacy varied with the primary tumor type, showing improved outcomes for patients with lung cancer (89.2%) versus other primary tumors (79.1%). Moreover, in non-outpatients, pain management was less effective for patients receiving radiotherapy on pelvic BMs (89.5%) compared with other sites (95.7%). Conclusion: Although overall rates of inadequate pain management were lower than seen in previous studies, significant variability exists based on patient health status, care setting, primary tumor type, and site of BMs. These results underscore the need for personalized pain management approaches and highlight specific areas for improvement in outpatient settings and among patients with generally good health but significant pain from BMs.